Cell Biology of Viral Infections - Lozach, Pierre-Yves (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Viruses exhibit an elegant simplicity as they are so basic, but so frightening. Although only a few are life threatening, they have substantial implications for human health and the economy, as exempliﬁed by the ongoing coronavirus pandemic. Viruses are rather small infectious agents found in all types of life forms, from animals and plants to prokaryotes and archaebacteria. They are obligate intracellular parasites, and as such, subvert many molecular and cellular processes of the host cell to ensure their own replication, ampliﬁcation, and subsequent spread. This Special Issue addresses the cell biology of viral infections based on a collection of original research articles, communications, opinions, and reviews on various aspects of virus-host cell interactions. Together, these articles not only provide a glance into the latest research on the cell biology of viral infections but also include novel technological developments.